Adult influenza epidemic is associated with out-of-hospital cardiac arrest: From the All-Japan Utstein Registry, a prospective, nationwide, population-based, observational registry. Issue 24 (17th June 2022) - Suematsu, Yasunori; Kuwano, Takashi; Yamashita, Motoki; Tsutsui, Hiroyuki; Sato, Naoki; Ikeda, Takanori; Nagao, Ken; Yonemoto, Naohiro; Tahara, Yoshio; Saku, Keijiro; Miura, Shin-ichiro
Abstract : Abstract: It has been reported that influenza infection is associated with out-of-hospital cardiac arrest of cardiac origin (OHCA-CA). However, the association between OHCA-CA and influenza epidemics in adults has not been well investigated. We analyzed data from the All-Japan Utstein Registry, a prospective, nationwide, population-based, observational study, regarding OHCA-CA cases and the Infectious Diseases Weekly Report for influenza cases: 17, 710 OHCA-CA cases and 764, 808 influenza cases were recorded between 2005 and 2015 in Fukuoka, Japan. The weekly average number of OHCA-CA cases was positively associated with the number of patients with influenza infection ( r  = 0.70, P  < .0001). To eliminate the effects of season and age, we investigated only adults in winter. The weekly number of OHCA-CA cases was positively associated with the number of patients with influenza infection in weeks when there was a high frequency of influenza infection in adults ( r  = 0.36, P  = .006), but not in weeks with a medium ( r  = 0.26, P  = .05) or low frequency of influenza infection ( r  = 0.003, P  = 1.0). In weeks during which there was a high frequency of influenza infection, the weekly number of OHCA-CA cases was positively associated with the number of influenza infections in males ( r  = 0.37, P  = .006), but not females ( r  = 0.18, P  = .2). The number of OHCA-CA cases was positively associated with the number of influenza infections in adult males during weeks in which there was a high frequency of influenza infections. To help prevent OHCA-CA in males, it might be beneficial to announce influenza epidemics specifically in adults, in addition to all ages.